Reação de resistência à giberela em cultivares de trigo (Triticum aestivum L.), avaliada em condições de campo e casa de vegetação - Alves, Rafael Hansen (2010)
Caused by several species of fungus, fusarium head blight (FHB) is a disease of great economic importance in wheat (Triticum aestivum L.), causing large losses in world grain production. In Brazil the main species of fungi responsible for disease is Gibberela zeae (Schwabe.), and its the anamorphic Fusarium graminearum (Schwabe). The control by chemical treatment of the disease with the use of fungicides has low efficiency due to the difficulty of identifying the exact time of application. Therefore, the use of resistant varieties is shown as a safe and economically viable alternative for the production of wheat scab-free. To contribute to the understanding of the behavior of some Brazilian wheat cultivars for FHB, the objectives were to assess the presence or absence of reaction to FHB resistance in wheat cultivars under inoculation in field conditions and greenhouse; and identify what kind of reaction that is acting (resistance type I or type II resistance). The proposed work was developed in the field, greenhouse and laboratory. Two methodologies inoculation were applied, depending on the type of resistance to be tested, and the targets of this work were to evaluate the resistance type I and type II resistance. Twenty eight genotypes with different responses to FHB resistance were used to both evaluations. The resistance of type I was measured by spraying the spikes with suspension. In the field, dispersal of inoculum in the area was used wheat grains colonized with perithecia previously inoculated. The assessment of disease severity in the 28 cultivars was made 21 days after inoculation (DAI), the green ear stage, taking on a note on a linear scale from zero to 100, based on the scale suggested by Stack and McMullen. The evaluation of resistance of type II was performed only in the greenhouse. Obtaining spore mass acquisition was performed by scraping the plates with PDA medium colonized by Fusarium graminearum. Conidia were washed with distilled water and received the inoculum. The concentration was adjusted to 5x104 spores per mL. The count was performed by an optical microscope with the aid of a Neubauer chamber. About 10μL of the suspension of spores (macroconidia) at a concentration of 5x104 mL-1 was injected between the lemma and palea of a spikelet located at the point of infection, on both sides of the ear, using a hypodermic syringe. Evaluations were performed at 7, 14 and 21 days after inoculation by counting the spikelets with symptoms of the disease, excluding the two infected spikelets. The FHB occurred in two periods in the field with greater variation among the 28 cultivars tested in the first season. For resistance type I, nine and nineteen cultivars had the lowest severity, respectively, in field and greenhouse conditions, showing that they are sources of resistance. In accessing the resistance of type II, BRS Umbu, CEP Nova Era, CEP Raizes, BRS 208 e Frontana not proved to be sources of resistance. Already BRS Guamirim, CD 120, Onix, Rubi, CEP 50, BRS 179, Pampeano, Abalone, CD 114, IPR 85, Safira, BRS Louro, CD 117, CDF 2002116, CD 115, BRS177, CD 0529 and BRS Camboim showed the lowest values for AUDPC thus demonstrating the potential for type II resistance to FHB